Negative controlled Fredkin gate circuits with mirrors. Issue 1 (6th December 2021) - Chattopadhyay, Tanay
Abstract: Data loss is a major problem in conventional circuits. But it cannot happen in reversible circuits. So energy dissipation per bit loss does not happen in this circuit. Also, recovery of input data can be possible in this circuit. Negative controlled Fredkin gate (NCF) is a self‐invertible reversible gate. It performs SWAP operation if its control input is logic zero. In this paper, a mechanically controlled mirror‐based NCF gate is designed, where the operation is based on the movement of mirrors. To move the mirror from its position electrical signal can be used. Optical signals are used in computational operations. Some complex reversible circuits viz. some logical operations (XOR‐XNOR, AND‐NAND, OR‐NOR), DE‐MUX/MUX, switching, and data shifting circuits are also shown in this paper. Quantum realization of the circuit was performed. Also, the matrix calculation was done to find out the operation of the circuit. Optical delay, optical cost, quantum delay, and quantum cost of every proposed design were calculated.